Next-Generation Proton-Exchange Membranes in Microbial Fuel Cells: Overcoming Nafion's Limitations - Sharma, Akshat; Đelević, Lara; Herkendell, Katharina (Energy Technology, 2024)
The adoption of microbial fuel cell (MFC) technology hinges on the development of efficient proton-exchange membranes (PEMs), which significantly influences fuel cell performance and cost. PEMs have a critical role in preventing oxygen crossover, maintaining electrochemical neutrality, and supporting microorganisms within MFCs. Nafion, the current industry-standard PEM, grapples with environmental, cost, and performance issues. Although improvements to Nafion have been reported using additives, immersion in heteropolyacids, different pretreatment methods, and UV irradiation, many of the challenges still remain. Herein, the recent developments in the area of alternative PEMs are reviewed and analyzed. Among them, sulfonated aromatic hydrocarbons, particularly sulfonated polyether ether ketone, have emerged as top contenders in terms of scale up and commercial viability. At the same time, membranes based on polyvinyl alcohol, ionic liquids, and natural materials are also being actively researched for various MFC applications. Since most studies are short term and lab scale, there is a need evaluate long-term stability and economic cost of PEMs in terms of standardized parameters such as power-to-cost and normalized energy recovery. Additionally, for emerging low-energy-density MFC applications like biosensors and in vivo power sources, PEM properties and design need to be tailored carefully.
CRIS-Team Scopus Importer:2024-03-29
Keywords: biofuel cells; cost analyses; membrane biofouling; membrane commercialization; microbial fuel cells; Nafion; proton exchange membranes